Hubungan Pengetahuan, Pendidikan dan Dukungan Keluarga dengan Penggunaan Alat Kontrasepsi Implant - Erlyna Evasari; Fitria Ayu Sahara (Jurnal Obstretika Scientia, 2017)
The study aims to identify the relationship among knowledge, education, and family support with the usage of contraceptive implant at Sindang Sari Village under the authority of Puskesmas Baros in 2016. The study is conducted using analytical survey and incorporates cross sectional design. The population of the study consists of 466 active contraceptive users. The sample of the study is 86 active contraceptive users. The result of the study indicates that there is a relationship among knowledge (p=0.028), education (p=0.000), and family support (p=0.001) with the usage of contraceptive implant. It is expected that the healthcare professionals to be able to give counselling on contraceptive, particularly implant, to women by using the help of media, such as poster, leaflet or even decision making tools (ABPK) to choose a suitable contraceptive, provide good service, and involve the family of the women, particularly the husbands, in giving the counselling on the types of contraceptive so that they can gain family support to choose the most suitable contraceptive for them.